Penerapan Pembelajaran Aqidah Akhlaq melalui Pendekatan Talaqqi di MA Ma’arif NU Kepung Kediri - Ja'far Shodiq (LPPM IAI Hasanuddin Pare-Kediri, 2017)
The development of learning methods that so rapidly in the past few years became a quite a relief phenomenon. But it is unfortunate that it is not directly proportional to the quality of learning outcomes. Many found alumni Madrasah Aliyah even college does not understand the science of religion well. Meanwhile, if we refer to the study of Islam in the time of the Prophet in fact the reality is reversed. At that time the method of learning is still very traditional and simple, that is by using Talaqqi method but the result is very good, proven at that time has been born human-human reliable, firm, courageous, and intelligent. The purpose of this research is (1) to know the application of talaqqi method in learning aqidah akhlaq in MA Ma'arif Kepung, (2) to know the obstacle and support of talaqqi method in MA Ma'arif NU Kepung. The author uses two data collection techniques at once, namelyAkket, Observation and interview. Data analysis technique used in this research is qualitative descriptive technique with percentage by using formula: P = x 100%. The conclusion of this research is (1) the application of talaqqi method in Learning Aqidah Akhlaq in MA Ma'arif NU Kepung is good, because the obtained percentage 84,19% .I